Isometric Contractions Are More Analgesic Than Isotonic Contractions for Patellar Tendon Pain: An In-Season Randomized Clinical Trial. Issue 3 (May 2017) - Rio, Ebonie; van Ark, Mathijs; Docking, Sean; Moseley, G. Lorimer; Kidgell, Dawson; Gaida, Jamie E.; van den Akker-Scheek, Inge; Zwerver, Johannes; Cook, Jill
Abstract : Objective: This study aimed to compare the immediate analgesic effects of 2 resistance programs in in-season athletes with patellar tendinopathy (PT). Resistance training is noninvasive, a principle stimulus for corticospinal and neuromuscular adaptation, and may be analgesic. Design: Within-season randomized clinical trial. Data analysis was conducted blinded to group. Setting: Subelite volleyball and basketball competitions. Participants: Twenty jumping athletes aged more than 16 years, participating in games/trainings 3 times per week with clinically diagnosed PT. Interventions: Two quadriceps resistance protocols were compared; (1) isometric leg extension holds at 60 degrees knee flexion (80% of their maximal voluntary isometric contraction) or (2) isotonic leg extension (at 80% of their 8 repetition maximum) 4 times per week for 4 weeks. Time under load and rest between sets was matched between groups. Main Outcome Measures: (1) Pain (0-10 numerical rating score) during single leg decline squat (SLDS), measured preintervention and postintervention sessions. (2) VISA-P, a questionnaire about tendon pain and function, completed at baseline and after 4 weeks. Results: Twenty athletes with PT (18 men, mean 22.5 ± 4.7 years) participated (isotonic n = 10, isometric n = 10). Baseline median SLDS pain was 5/10 for both groups (isotonic range 1-8, isometric range 2-8). Isometric contractions produced significantly greater immediate analgesia ( P < 0.002). Week one analgesic response positively correlated with improvements in VISA-P at 4 weeks (r 2 = 0.64). Conclusions: Both protocols appear efficacious for in-season athletes to reduce pain, however, isometric contractions demonstrated significantly greater immediate analgesia throughout the 4-week trial. Greater analgesia may increase the ability to load or perform.